2007
DOI: 10.1093/ajcn/86.5.1486
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of dietary pattern and risk of Parkinson disease

Abstract: (1986 -2002) and the Nurses' Health Study (1984 -2000). Design: We included 49 692 men and 81 676 women free of PD at baseline and used principal components analysis to identify major dietary patterns and the Alternate Healthy Eating Index (AHEI) and the alternate Mediterranean Diet Score (aMed) to assess diet quality. Relative risks (RRs) were computed by using Cox proportional hazards models within each cohort and were pooled by using a random-effects model. Results: We documented 508 new PD cases after 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
236
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(262 citation statements)
references
References 48 publications
12
236
2
7
Order By: Relevance
“…This dietary pattern has also been associated with lower risk of cerebrovascular disease (6) and working memory (7). Mediterranean diets are also associated with lower rates of dementia (8,9), and other neurodegenerative diseases such as Alzheimer's disease (AD) (10) and Parkinson's disease (11). Basic research suggests that naturally occurring phytocompounds, such as polyphenolic antioxidants found in fruits, vegetables, herbs and nuts, may potentially inhibit or slow down neurodegeneration, and improve cognitive function (12).…”
Section: Introductionmentioning
confidence: 99%
“…This dietary pattern has also been associated with lower risk of cerebrovascular disease (6) and working memory (7). Mediterranean diets are also associated with lower rates of dementia (8,9), and other neurodegenerative diseases such as Alzheimer's disease (AD) (10) and Parkinson's disease (11). Basic research suggests that naturally occurring phytocompounds, such as polyphenolic antioxidants found in fruits, vegetables, herbs and nuts, may potentially inhibit or slow down neurodegeneration, and improve cognitive function (12).…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress apparently promotes the aggregation of alpha-synuclein. 187 A reduced risk of Parkinson's disease has been observed for [188][189][190] which did not distinguish between alcoholic beverages. Such a reduced risk has, however, been specifically shown for wine consumers where an inverse relationship between amount of wine consumed and risk was observed; the lowest risk was observed for wine consumers of approximately 140 to 420 g alcohol/week.…”
Section: Effect Of Wine On Parkinson's Diseasementioning
confidence: 97%
“…Epidemiological studies found that high intake of fruits, vegetables and fish was inversely associated with PD risk (Gao et al, 2007;Okubo et al, 2012 characteristic of a Mediterranean diet, are emerging as a potential neuroprotective alternative for PD (Alcalay et al, 2012). Most fruits and vegetables are rich sources of antioxidants, including vitamins A, B (riboflavin), C, and E, which are present in low levels in some PD patients.…”
Section: Nutrients That May Be Associated With a Decreased Risk Or Prmentioning
confidence: 99%